2018
DOI: 10.18178/ijmerr.7.5.534-543
|View full text |Cite
|
Sign up to set email alerts
|

An Ergonomic Student Chair Design and Engineering for Classroom Environment

Abstract: Classroom chair is considered as an important element for students to improve comfort and concentration in study environment. An ergonomic chair design and engineering is therefore considered very important for its usability and comfort point of views for the students. An ergonomic chair ensures better comfort and confidence for the students in a classroom environment. This research study is proposed an innovative ergonomic chair design and engineering with the objective to satisfy all the basic needs of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Products are design based on specific functions that benefit users. However, their successful function is dependent on its usability for people [ 1 , 2 ]. The furniture’s function is to facilitate learning and provide a convenient, stressless environment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Products are design based on specific functions that benefit users. However, their successful function is dependent on its usability for people [ 1 , 2 ]. The furniture’s function is to facilitate learning and provide a convenient, stressless environment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classroom furniture is a critical factor for the adoption of proper postures. Consequently, it has implications for the students’ learning productivity [ 5 ] and students’ comfort in the study environment [ 1 ]. In educational ambiances, anthropometry has become a crucial discipline.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our study showed that persons weighing between 89.800 kg and 99.960 kg can safely work at a desk whose worktop is tilted 30 0 , without compromising the permissible spine load of 3400N. The disadvantage of student sitting caused by inadequate chair and bench design results very often in the overload of the student's spinal column, and consequently the resulting skeletal deviations that can result from it [8]. It has been found that more and more problems occur when office workers are sitting in a modern business environment [9].…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, the use of sharp corners in furniture and walls should be avoided to prevent injuries, bruises and unwanted stumbling (Kilbourne et al , 2017). Also, windows need to be designed at a suitable height to ensure student safety when sitting and standing on their seats or walking close to the walls to save them from accidentally hitting the panes (Al-Hinai et al , 2018). Whiteboards, smart boards or traditional boards should be installed at an appropriate height to ensure visibility to everyone sitting in the room (Clinton and Wilson, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%